2013
DOI: 10.1002/ece3.492
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origin of Leucobryum boninense Sull. & Lesq. (Leucobryaceae, Musci) endemic to the Bonin Islands, Japan

Abstract: Leucobryum boninense is endemic to the Bonin Islands, Japan, and its related species are widely distributed in Asia and the Pacific. We aimed to clarify the phylogenetic relationships among Leucobryum species and infer the origin of L. boninense. We also describe the utility of the chloroplast trnK intron including matK for resolving the phylogenetic relationships among Leucobryum species, as phylogenetic analyses using trnK intron and/or matK have not been performed well in bryophytes to date. Fifty samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The discoveries of genetically distinct groups within the morphologically similar complex have driven more detailed morphological studies to find the defining characteristics of the observed genetic groups, which subsequently enhance our ability to perform taxonomic revision ( Renner 2020 ). Several species complexes in Leucobryum have been recognized ( Patterson et al 1998 ; Vanderpoorten et al 2003 ; Oguri et al 2006 ; Oguri et al 2008 ; Oguri et al 2013 ). For example, L. glaucum (Hedw.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discoveries of genetically distinct groups within the morphologically similar complex have driven more detailed morphological studies to find the defining characteristics of the observed genetic groups, which subsequently enhance our ability to perform taxonomic revision ( Renner 2020 ). Several species complexes in Leucobryum have been recognized ( Patterson et al 1998 ; Vanderpoorten et al 2003 ; Oguri et al 2006 ; Oguri et al 2008 ; Oguri et al 2013 ). For example, L. glaucum (Hedw.)…”
Section: Discussionmentioning
confidence: 99%
“…Similar to many moss genera, the moss genus Leucobryum Hampe has been shown to include several cryptic species ( Oguri et al 2006 ; Oguri et al 2010 ; Oguri et al 2013 ; Bonfim Santos and Stech 2017 ). The genus currently includes about 80–100 species worldwide with predominantly temperate and tropical distribution ( Eddy 1990 ; Enroth 1990 ; Klazenga 2012 ).…”
Section: Introductionmentioning
confidence: 99%